Antagonistic Properties Of Certain Biocontrol Agents Against Fusarium Oxysporum F. Sp. Lycopersici And Sclerotium Rolfsii (Journal of Plant Disease Sciences, 2021)
Wilt and Collar rot is devasting disease of tomato and brinjal cop respectively responsible for low production and productivity. Being soil borne pathogens difficult to control with chemical fungicides. Hence a study was undertaken to determining the efficacy of seven biocontrol agents in the management of fungus Fusarium oxysporum f.sp. lycopersici and Sclerotium rolfsii Sacc in vitro. The biocontrol agent Trichoderma harzianum showed highest growth inhibition (54.33%) and (54.14%) of both Fusarium oxysporum f.sp. lycopersici and Sclerotium rolfsii Sacc over untreated control. Next best were T. hamatum, M. anisopliae, T. virens and T. asperellum. Among all bioagent tested, least per cent inhibition of the pathogen was observed in treatment of V. lecanii.
Keywords: Brinjal; Biocontrol agents; Collar rot; Tomato and Wilt